2011
DOI: 10.1159/000334097
|View full text |Cite
|
Sign up to set email alerts
|

Somatotopic Location of Corticospinal Tracts in the Internal Capsule with MR Tractography

Abstract: We demonstrated the exact location of the somatotopic area of the corticospinal tract in the internal capsule. Ten healthy subjects participated in this study. We used the imaging technique that combines functional magnetic resonance imaging and diffusion tensor tractography. In order to reduce erroneous elements while image processing, we used the probabilistic tracking algorithm and brain normalization method. Our results showed that hand fibers were located anteromedial to foot fibers, and the separation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Corticobulbar and corticospinal tract degeneration are phenotype‐defining features of ALS, yet these tracts are rarely examined separately and correlated with clinical disability. These tracts are relatively well separated in the internal capsule (IC) where corticobulbar tracts run in the genu of the IC and CSTs run in the posterior limb of the IC in a somatotopic arrangement, representing the upper extremity, trunk, lower extremity in an anteromedial to posterolateral anatomical organization . Spastic speech, dysphagia, positive jaw‐jerk and pseudobulbar affect are just some of the frequently observed symptoms in ALS that can be directly linked to corticobulbar tract dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Corticobulbar and corticospinal tract degeneration are phenotype‐defining features of ALS, yet these tracts are rarely examined separately and correlated with clinical disability. These tracts are relatively well separated in the internal capsule (IC) where corticobulbar tracts run in the genu of the IC and CSTs run in the posterior limb of the IC in a somatotopic arrangement, representing the upper extremity, trunk, lower extremity in an anteromedial to posterolateral anatomical organization . Spastic speech, dysphagia, positive jaw‐jerk and pseudobulbar affect are just some of the frequently observed symptoms in ALS that can be directly linked to corticobulbar tract dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the somatotopic location of CST in the CR is an important consideration for the patients with brain injury because the lesions of brain injury are commonly located on the CR. Recently, many studies have been done for elucidating the somatotopic location of CST using diffusion-tensor tractography (DTT), which derived from diffusion-tensor image (DTI), combined with other technical methods such as functional magnetic resonance imaging (fMRI) (Holodny et al, 2005a,b; Hagmann et al, 2006; Smits et al, 2007; Mukherjee et al, 2008; Mancini et al, 2009; Suzuki et al, 2009; Masri, 2011; Jang, 2011; Lee et al, 2012; Seo et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Using the orientation convention used in the present paper (Fig. 2), the hand was described to be either lateral (Holodny et al, 2005; Ino et al, 2007) or anterior to the foot fascicle (Ino et al, 2007; Lee et al, 2012; Park et al, 2008). A study using direct white matter electrical stimulation in the PLIC area reported a face-anterior, arm-intermediate and leg-posterior somatotopic organization (Duerden et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several diffusion tensor imaging (DTI)-based studies have observed differences in somatotopic organization. For instance, in the long axis of the corona radiata (CR) and the posterior limb of the internal capsule (PLIC), hand fascicles were either anterolateral to foot fascicles at the CR (Lee et al, 2014; Seo et al, 2012) and PLIC (Park et al, 2008) or anteromedial at the PLIC (Lee et al, 2012). Other studies found the hand fascicles to be anterolateral to the foot fascicles and partially overlapping relationships have been observed at lower levels (Holodny et al, 2005; Ino et al, 2007; Smits et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation